An Empirical Analysis of the Integration-Responsiveness Framework in Global Industries - Roth, Kendall; Morrison, Allen J. (Journal of International Business Studies, 1990)
In this study, businesses competing in global industries were categorized into three groups according to the integration-responsiveness framework for conceptualizing industry pressures confronting business competing internationally. Using this framework, contextual conditions associated with each group were examined. Competitive attributes distinguishing each group were then identified to clarify alternate business-level strategies for competing within a global industry context. Beyond providing additional insight into the nature of competition in global industries, several broad extensions to the integration-responsiveness framework are suggested.